2019
DOI: 10.1073/pnas.1902012116
|View full text |Cite
|
Sign up to set email alerts
|

LSD1 destabilizes FBXW7 and abrogates FBXW7 functions independent of its demethylase activity

Abstract: FBXW7 acts as a typical tumor suppressor, with loss-of-function alterations in human cancers, by promoting ubiquitylation and degradation of many oncoproteins. Lysine-specific demethylase 1 (LSD1) is a well-characterized histone demethylase. Whether LSD1 has demethylase-independent activity remains elusive. Here we report that LSD1 directly binds to FBXW7 to destabilize FBXW7 independent of its demethylase activity. Specifically, LSD1 is a pseudosubstrate of FBXW7 and LSD1-FBXW7 binding does not trigger LSD1 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 51 publications
4
53
0
Order By: Relevance
“…However, there are some differences in the mechanism. According to Chao's and Lan's studies, LSD1 destabilizes target protein independent of its demethylase activity (Chao et al, ; Lan et al, ). In our study, LSD1 regulates the transcription of p62 depending on its demethylase activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some differences in the mechanism. According to Chao's and Lan's studies, LSD1 destabilizes target protein independent of its demethylase activity (Chao et al, ; Lan et al, ). In our study, LSD1 regulates the transcription of p62 depending on its demethylase activity.…”
Section: Discussionmentioning
confidence: 99%
“…This is relevant because in the majority of AML cases, TP53 is not mutated and it can be re-activated (95). KDM1A also binds as pseudosubstrate to the tumor suppressor and ubiquitin ligase FBXW7 (96). This results in FBXW7 auto-ubiquitination and subsequent proteasomal and lysosomal degradation.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…As depicted in Fig. 3 E, we found that PKM2 was polyubiquitinated by wild-type FBW7α, but not the enzymatically dead mutant (ΔF-box-FBW7) [ 34 ] ( Fig. 4 E).…”
Section: Resultsmentioning
confidence: 99%